Invariant temporal order of replication of the four actin gene loci during the naturally synchronous mitotic cycles of Physarum polycephalum. - Pierron, G (1984)
The chronological sequence of replication for the four unlinked actin gene loci of Physarum has been established. Southern hybridization analysis of density-labeled, bromodeoxyuridine-substituted DNA isolated from defined periods of S phase demonstrates that three actin loci (ardB, ardC, ardD) are duplicated early, corresponding to the first 10% of the genome. The fourth locus (ardA) replicates later, between 80 and 100 min into S phase and after 75% of DNA synthesis is completed. Gene-dosage determinations, based on the quantitation of hybridization signals from DNAs isolated from various times during S phase, confirm the results obtained with bromodeoxyuridine-substituted DNA and increase the temporal resolution. The chronological order of replication in the macroplasmodium appears constant through two consecutive cell cycles and after prolonged growth in suspension culture. The precise chronology of DNA synthesis at the gene level extends to the coordinate replication of allele pairs.